Mental Health Issues Among Indigenous Communities and the Role of Traditional Medicine - Iswanto; Dewi Maryam; Ratna Puji Priyanti; Eva Felipe Dimog; Asri (Universitas Nahdlatul Ulama Surabaya, 2026)
Indigenous populations worldwide face significant mental health disparities stemming from historical trauma, colonization, and marginalization. The World Health Organization reports particularly concerning rates of suicide and self-harm among indigenous youth. These communities struggle with multiple interconnected challenges, including economic hardship, limited access to education, and identity crises. This narrative review es mental health issues among indigenous communities and the role of traditional medicine in addressing these challenges. This review analyzed sources from 2014 to 2024 in English and Bahasa Indonesia, including academic papers, government reports, and grey literature on indigenous peoples, mental illness, and traditional medicine. Using keywords related to indigenous/aboriginal communities, mental health, and traditional/alternative medicine, the review presented findings across 5 themes: Indigenous community challenges; health and cultural perspectives; traditional and biomedical approaches; preservation of traditional medicine; and new healthcare models. Traditional medicine faces challenges from systematic marginalization and younger generations' skepticism. The review advocates for an integrated healthcare approach that combines traditional and biomedical practices while preserving indigenous knowledge systems. This integration requires cultural competency, specialized training for healthcare professionals, and empowerment of indigenous community members in healthcare roles.